Review of Roger Ames and David Hall, Daodejing: Making This Life Significant: A philosophical translation - CHAN, Alan Kam Leung (Institutional Knowledge at Singapore Management University, 2005)
Is there a need for another translation of the Laozi Daodejing? Although there are already over 100 translations in English alone, this present effort by Ames and Hall marks a welcome addition, in that it offers an engaging philosophical account of the Daodejing as chiefly concerned with “making this life significant.”